基于端面滚切法加工的锥齿轮齿面测量研究 - 聂少武; 邓效忠; 李天兴; 邓静; 周广才 (Jixie chuandong)
Aiming at tooth surface accuracy of bevel gear by face hobbing,the tooth surface error measuring is studied on domestic gear measurement center.The measuring principle is analyzed,and the measuring area and measuring path are planned,and the mathematical model of the bevel gear is established,and the theoretical tooth surface is calculated.The coordinates of probe radius and deformation are compensated,through coordinate transformation between work system and measuring machine system,and the theoretical coordinates of probe center which are used to control measuring movement are obtained,and the tooth surface error equation is established according to actual measured data.Finally the measuring software of tooth surface accuracy is developed on domestic gear measurement center,and the result demonstrates that the measuring method is feasible and correct by measuring experiment.